2018
DOI: 10.1155/2018/9658707
|View full text |Cite
|
Sign up to set email alerts
|

The Ideotype for Seed Size: A Model Examining the Relationship between Seed Size and Actual Yield in Pea

Abstract: Seed size plays a large role in determining productivity of large seeded legumes. In many large seeded legumes such as pea and bean, actual yield, defined here as grain yield at harvest minus the weight of seed planted, is often a better measure of actual productivity than grain yield at harvest, because the weight of planted seed varies with seed size. In many grain legumes, the weight of planted seed can be equal to 10% of the total grain yield, and minimizing the weight of planted seed could significantly i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Seed is the start and end points of plant life, and the important determinants of growth and development. Seed size is a key agronomic characteristic of evolutionary fitness in plants during domestication and breeding in many crops with seeds as the main product organ, and a key factor affecting seed yield, eating quality, tolerances to environmental stresses (Song et al, 2007;Bai et al, 2010;Gu et al, 2017;Smitchger and Weeden, 2018). In general, large seeds have more advantages than small ones in crop production because large seeds have bigger endosperm or cotyledons that can provide more nutrients for seedling establishment (Chen et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Seed is the start and end points of plant life, and the important determinants of growth and development. Seed size is a key agronomic characteristic of evolutionary fitness in plants during domestication and breeding in many crops with seeds as the main product organ, and a key factor affecting seed yield, eating quality, tolerances to environmental stresses (Song et al, 2007;Bai et al, 2010;Gu et al, 2017;Smitchger and Weeden, 2018). In general, large seeds have more advantages than small ones in crop production because large seeds have bigger endosperm or cotyledons that can provide more nutrients for seedling establishment (Chen et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…They found that the normalized pixel area of the rice kernel predicts the single kernel weight with 0.95% accuracy. Smitchger and Weeden (2018) found the ideal seed size for maximum seed yield in pea plants and reported that the seeds with the maximum size had the highest seed weight and harvest index. However, in all these cases, the main focus was on in-field plant traits to predict the soybean seed weight.…”
Section: Resultsmentioning
confidence: 99%
“…This finding suggested that compared with the intolerant group, the tolerant group had more photosynthates to consume to form a higher number of seeds. The increase in the number of seeds in the tolerant group was closely related to photosynthate production (Smitchger and Weeden 2018).…”
Section: Yield and Yield Components Numbers Of Pods Seeds And Seed We...mentioning
confidence: 91%